Der Verlust der Identität: Zu den Romanen von Siegfried Lenz - Schlosser, Jan (Nordlit, 2011)
The article focuses on the topic of identity crises in the novels of German author Siegfried Lenz. He presents no solution of the identity problem, which is reflected both in a private and in a historical dimension, but has a distinct preference for nostalgic ways of life.